Studi Komparatif Penggunaan Metode Diskusi Dan Metode Ceramah Dalam Pembelajaran Ips Di SMP Negeri 2 Indrajaya - Yusrita Maulisa; Darmi Darmi; Maisura Maisura (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2026)
This study aims to determine the effectiveness of the discussion method compared to the lecture method in improving students' understanding of Social Studies at SMPN 2 Indrajaya. The background of the problem is the low student learning outcomes due to the dominance of conventional teaching methods. This research employs a quantitative approach with a quasi-experimental design involving class VIII A as the experimental group and class VIII B as the control group, each consisting of 26 students. The sampling technique used was purposive sampling. The analysis results showed that the Z-count (5.324) was greater than the Z-table (2.957), indicating a significant difference between the two methods. The average N-Gain score of the experimental class was 80.38% (high category), while the control class obtained 76.35% (medium category). Thus, the discussion method is proven to be more effective and has a significant impact on improving student learning outcomes.